Child and youth protagonists in Habila’s Measuring Time and Dangor’s Bitter Fruit - Akpome, Aghogho (Tydskrif vir Letterkunde, 2018)
Helon Habila’s Measuring Time and Achmat Dangor’s Bitter Fruit deploy child and youth protagonists to offer nuanced perspectives on contemporary nationhood in Nigeria and South Africa respectively, displacing the adult, and mostly male viewpoints that have dominated novelistic portrayals of postcolonial nationhood for decades. These protagonists are portrayed symbolically in the context of the biological family, which can be read in allegorical and metonymic ways to represent the nation as a social unit. This article explores the portrayal of these protagonists and their families for the ways in which they may reflect national anxieties in general, and the problems of recent socio-political transition in particular. It also highlights how the breakdown of the family, as well as the different pathways undertaken by characters may represent simultaneously dystopian and auspicious futures for Nigeria and South Africa.